2018
DOI: 10.2134/jeq2018.05.0181
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Phosphorus Release Is Limited by High pH and Excess Calcium

Abstract: Aside from its use for improving soil properties, biochar is increasingly promoted as a direct nutrient provider for sustainable recycling of waste materials. However, incomplete understanding of the interacting factors that determine P release from biochar may limit the efficiency of P recycling from biochar to soil. In particular, the contrasting pH of biochar and soil need to be considered. In this study, soil‐free biochar (rice [Oryza sativa L.] husk, 700°C) extractions were performed under different pH (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This may be a contributing factor to the decreased PO 4 -P content observed from T 1 to T 2 . A similar finding was reported by Buss et al (2018), where a reduction in P release from BC over a series of extractions was observed. Almost 17% of the total P content (258 ± 2.9 mg kg −1 ) was initially released in the first extraction step, and successively less P at the second (137 ± 2.4 mg kg −1 ) and sixth (34 ± 0.8 mg kg −1 ) extraction steps.…”
Section: Phosphorous (Po 4 -P)supporting
confidence: 89%
See 1 more Smart Citation
“…This may be a contributing factor to the decreased PO 4 -P content observed from T 1 to T 2 . A similar finding was reported by Buss et al (2018), where a reduction in P release from BC over a series of extractions was observed. Almost 17% of the total P content (258 ± 2.9 mg kg −1 ) was initially released in the first extraction step, and successively less P at the second (137 ± 2.4 mg kg −1 ) and sixth (34 ± 0.8 mg kg −1 ) extraction steps.…”
Section: Phosphorous (Po 4 -P)supporting
confidence: 89%
“…The optimal pH range for the availability of P to plants is 6.0-6.5 (Buss et al 2018), which all soil types were approaching during the course of this study i.e. from T 1 to T 2 (see Fig.…”
Section: Phosphorous (Po 4 -P)mentioning
confidence: 88%
“…Meta‐analyses have found that biochar application commonly increases P availability, particularly when applied to acidic or neutral soils, and for biochar produced from low C:N feedstocks (e.g., manure, crop residues), and produced at low temperatures (Gao et al, 2019; Glaser & Lehr, 2019). However, P availability can be low in Ca‐rich and K‐poor feedstocks such as sewage sludge (Buss et al, 2018, 2020; Torres‐Rojas et al, 2020; Wang et al, 2019) because pyrolysis can convert plant‐available organic P into inorganic P that is less available in the short term (Buss et al, 2020; Rose et al, 2019). The opposite has also been observed, with pyrolysis increasing plant‐available P although decreasing water‐extractable P (Wang et al, 2014; Zwetsloot et al, 2015, 2016).…”
Section: Mechanisms Of Biochar Effects On Soil and Plantsmentioning
confidence: 99%
“…The opposite has also been observed, with pyrolysis increasing plant‐available P although decreasing water‐extractable P (Wang et al, 2014; Zwetsloot et al, 2015, 2016). The effect of biochar on P availability is determined by microscale effects on soil pH and soil solution composition, especially Ca content (Buss, Assavavittayanon, et al, 2018; Buss et al, 2018). Biochar can retain nutrients, especially N, released as fertilizers dissolve, and nutrients already present in soil, reducing loss through leaching (Haider et al, 2020).…”
Section: Mechanisms Of Biochar Effects On Soil and Plantsmentioning
confidence: 99%
“…These factors interact to determine the P that is available inside and around biochar TA. High levels of Ca could limit the release of P from the high-pH interior of VCZ and Reference biochar (Buss et al 2018). The proportional decrease in available P from VCZ biochar treatments was, however, signi cantly smaller than for TSP fertilizer.…”
Section: Morphological and Spatial Root Responses To Sources Of Phosphorusmentioning
confidence: 99%